TNF-alpha releasing capacity of the whole blood drops after open total splenectomy, but increases after partial/subtotal or minimally invasive splenectomy. Issue 5 (3rd September 2022) - Dragomir, Mihnea P.; Tudor, Stefan; Lacatus, Monica; Stanciulea, Oana; Trandafir, Bogdan; Diaconu, Adriana; Coriu, Daniel; Colita, Anca; Droc, Gabriela; Purnichescu-Purtan, Raluca; Calin, George; Vasilescu, Catalin
Abstract: Background: The mechanisms that induce immunodeficiency after splenectomy remain unknown. The aim of this study was to measure the cytokine releasing capacity of the whole blood as an expression of the innate immunity after total (TS) and subtotal/partial splenectomy (S/PS) in order to assess the impact of splenectomy on the individual cytokine reactivity. Methods: We prospectively collected blood before (D0) and at multiple time points after splenectomy (7 days - D7, 30 days - D30, 90 days - D90, 180 days - D180, and 360 days - D360) and measured the cytokines releasing capacity of IL-6, TNF-alpha and IL-10 from whole blood under LPS stimulation which we normalized to the monocytes number. Results: When analyzing all splenectomies at D0, D7 and D30, normalized ΔTNF-alpha significantly dropped after splenectomy ( p = .0038) and normalized ΔIL-6 and ΔIL-10 did not significantly change. More specifically, normalized ΔTNF-alpha dropped after TS ( p = .0568) and significantly increased after S/PS ( p = .0388). Open surgery induced a decrease in normalized ΔTNF-alpha ( p = .0970), whereas minimally invasive (MI) surgery significantly increased the normalized ΔTNF-alpha releasing capacity ( p = .0178). The cytokine levels were heterogenous between pathologies at D0, and ΔIL-6 dropped mainly in cirrhotic patients after splenectomy (all underwent TS), ΔTNF-alpha dropped in immune thrombocytopenic purpura patients (all underwent TS), but increased in spherocytosis (91% underwent S/PS) after splenectomy. Conclusions: Splenectomy induces a decrease of the pro-inflammatory cytokine TNF-alpha and if splenic parenchyma is spared and the surgery is performed MI, this change is hindered.